Determinants of financial inclusion in Afar Region: Evidence from selected woredas - Esmael Abdu; Mohammd Adem (Cogent Economics & Finance, 2021)
This paper examined the determinants of financial inclusion in Afar Region. To address the objectives of the study, two purposively selected woredas (Awash and Asaita) and one city administration (Samara-logia) were used. Three hundred and eighty-four sample households were selected for this study. Data collected from administered structured questionnaires were analyzed using the binary logistic regression model. The results show that age, use, financial literacy, and mobile banking are positively and significantly related to financial inclusion. On the other hand, barrier and income negatively and significantly affect financial inclusion. The study results reveal that 31.25% of households were included and 68.75% of households are excluded from formal financial services. Further results show that barriers to financial inclusion such as problem of access to credit, absence of collateral, interest rate, lack of literacy, lack of internet access, lack of trust for financial institutions, lack of money, problem of access to bank branches and ATMs are main obstacles of financial inclusion in Afar region. This study recommends that government and financial institutions should encourage financial service providers, offer fiscal incentives or request financial institutions and serve poor or low-income people. Financial institutions should adopt technologies that ensure financial services are more accessible such as mobile banking. Moreover, households should enhance the saving habits that are helpful to increase amount of income and the literacy level of their children for the best use of financial services.
Keywords: 330; Afar region; financial inclusion; financial institution; logit regression